Dacryocele in an adult presenting as facial cellulitis - Kansakar, Prerana; Sundar, Gangadhara (Grande Medical Journal, 2019)
A 47-year-old male presented with left sided facial cellulitis of one-week duration associated with a painful mass over the left medial canthal area. On examination, there was a firm, tender mass below the medial canthal tendon. Computed tomography scan revealed a bulky, cystic lesion at the left inferomedial orbit and medial maxilla with bony remodeling suggestive of a chronic dacryocele. The patient underwent marsupialization of the dacryocele at the inferior meatus with silicone tube intubation. His symptoms of epiphora resolved after surgery. We describe a rare clinical presentation of dacryocele in an adult and its simple, yet effective treatment option.